On the influence of aluminium and iron impurities on the thermal contraction of an argon arc - Porytskyy, P.V. (Вопросы атомной науки и техники, 2008)
The influence of metal impurities on the process of contraction (self-constriction) of an arc discharge is considered in the ambient atmosphere of argon. The calculations are carried out, and it is shown that the degree of constriction of an arc discharge is determined by both the thermal characteristics of the gaseous medium and the characteristics of electron-atom collisions. It is shown the possibility to neutralize the influence of the Ramsauer effect on a character of the contraction of an arc.